Investigação fitoquímica e bioatividade de espécies de Euphorbiaceae da Caatinga - Abreu, Lucas Silva (2020)
Natural products have been used as a treatment option for diseases since ancient times. In this context, Brazil has one of the main biodiversities in the world. Among Brazilian biomes, the caatinga has vegetation that supports low rainfall and becomes a region with more endemic species. In this biome are several species of medicinal uses, including the Euphorbiacea family with reports of various biological activities. In this context, the study describes the phytochemical study of the species Stillingia loranthacea and Croton velutinus from the northeastern caatinga. The species were collected in the city of Morro do Chapéu -Bahia. It was used maceration as extraction technique in order to obtain the extracts, and classical chromatography on open column forinitial fractionation. For the isolation of chemical components, High Performance Liquid Chromatography on Analytical, Semi and Preparative Scales was used, when necessary mass spectrometry was also appliedto perform a targeted treatment, which was the basic information to molecular network data. The compounds had their structures determined by 1H and 13CNMR spectroscopicdata in one and two dimensions, spectrometric data for molecular and structural confirmation, infrared, optical rotation and comparison with data available in the literature. From the root barks ofS. loranthacea fourteen compounds were isolated, fournew derivate of the 28-taraxarene skeleton(SL1-SL4), four new tigliane diterpenes(SL5-SL8), three known tigliane diterpene(SL9-SL11)and three known flexibilines(SL12-SL14). The cytotoxicity and antiviral activity of compounds (SL1,SL2,SL5-SL14) were evaluated against Vero cells and against epidemic zika virus (ZIKV) circulating in Brazil. Six among the twelve compounds (SL2, SL5, SL9-SL11and SL14) had significant antiviral effect against ZIKV. Specifically, compounds SL2 and SL5 were the most promising compounds. From the roots of C. velutinus, four new phenylpropanoid (CV1-CV4) and three knowns (CV5-CV7) were isolated. The anti-inflammatory, cytotoxic and trypanocidal activities of the compounds were evaluated. Only compounds CV2 and CV5 showed cytotoxic activity forcancer celllines (B16F10, HL-60, HCT116, MCF-7 and HepG2), as well as trypanocidal activity. All compounds decreased the production of nitritein macrophages J774, just the CV5 compound decreased the production ofIL-1β